The fight against doubt : how to bridge the gap between scientists and the public - Melo-Martín, Inmaculada de; Intemann, Kristen (Oxford University Press, 2018)
Dissent about widely accepted scientific claims can promote doubt about scientific evidence, intimidate scientists, stymie research, and lead the public and policymakers to oppose needed policies. To limit these problems, The Fight against Doubt calls for facilitating greater trust between scientists and laypersons and recognizing the limits of science in policymaking.